2015
DOI: 10.17507/tpls.0501.27
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Iranian EFL Teachers’ Leadership in English Language Institutes

Abstract: Abstract-Researchers have demonstrated that effective teacher leadership has a positive influence on English language students' achievement and it is seen as an essential means for institution improvement and renewal. To this end, the present article aimed at exploring and quantitatively analyzing the extent to which EFL teachers perceive teacher leadership. Therefore, through the adoption of a Questionnaire of Teacher Leadership School Survey ( presented in appendix B) developed by Katzenmeyer and Moller (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Furthermore, Koosha, Liaghat, and Sadeghdaghighi (2015) analyzed Iranian EFL teachers' leadership in English Language centers by means of a questionnaire created by Katzenmeyer and Moller (2009). They concluded that the majority of EFL instructors practised and employed a standard level of instructor leadership in their classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Koosha, Liaghat, and Sadeghdaghighi (2015) analyzed Iranian EFL teachers' leadership in English Language centers by means of a questionnaire created by Katzenmeyer and Moller (2009). They concluded that the majority of EFL instructors practised and employed a standard level of instructor leadership in their classes.…”
Section: Literature Reviewmentioning
confidence: 99%